Targeted deep sequencing of plasma circulating cell-free DNA reveals Vimentin and Fibulin 1 as potential epigenetic biomarkers for hepatocellular carcinoma. - Reetta Holmila; Athena Sklias; David C Muller; Davide Degli Esposti; Paule Guilloreau; James Mckay; Suleeporn Sangrajrang; Petcharin Srivatanakul; Pierre Hainaut; Philippe Merle; Zdenko Herceg; Andre Nogueira da Costa (PLoS ONE)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer death worldwide, but is still lacking sensitive and specific biomarkers for early diagnosis and prognosis. In this study, we applied targeted massively parallel semiconductor sequencing to assess methylation on a panel of genes (FBLN1, HINT2, LAMC1, LTBP1, LTBP2, PSMA2, PSMA7, PXDN, TGFB1, UBE2L3, VIM and YWHAZ) in plasma circulating cell-free DNA (cfDNA) and to evaluate the potential of these genes as HCC biomarkers in two different series, one from France (42 HCC cases and 42 controls) and one from Thailand (42 HCC cases, 26 chronic liver disease cases and 42 controls). We also analyzed a set of HCC and adjacent tissues and liver cell lines to further compare with 'The Cancer Genome Atlas' (TCGA) data. The methylation in cfDNA was detected for FBLN1, PSMA7, PXDN and VIM, with differences in methylation patterns between cases and controls for FBLN1 and VIM. The average methylation level across analyzed CpG-sites was associated with higher odds of HCC for VIM (1.48 [1.02, 2.16] for French cases and 2.18 [1.28, 3.72] for Thai cases), and lower odds of HCC for FBLN1 (0.89 [0.76, 1.03] for French cases and 0.75 [0.63, 0.88] for Thai cases). In conclusion, our study provides evidence that changes in VIM and FBLN1 methylation levels in cfDNA are associated with HCC and could represent useful plasma-based biomarkers. Also, the potential to investigate methylation patterns in cfDNA could bring new strategies for HCC detection and monitoring high-risk groups and response to treatment.